REPOSITIONING BRAND SHIBOTIK UNTUK MEMBANGUN CITRA BARU SEBAGAI BATIK LIMITED EDITION - Fitri Nurlaili; Sandy Rismantojo (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
Positioning holds an important role in a branding activity; it enables a product to stand out in the minds of consumers compared to other competitor. If there is some fault in positioning, it will impact badly on a brand. It happens to one of Indonesian local brand, Shibotik. Shibotik combines traditional Japanese manual resist dyeing technique (Shibori) and Indonesian batik techniques, to produce an innovation in batik development so that it will give a wide variety of consumers in buying batik. Shibotik sells their product quite expensive, but the brand positioning is not suitable with goals that have been set on, which doesn't create an impression of limited edition products for the desired target. To overcome the problem issued above, repositioning need to be made so that Shibotik could construct an image as limited edition batik, with 24-40 years old woman as the main target. Before making this design several methods were carried out, namely the method of observation, questionnaires, interviews and literature. To give an unique concept in the design, a clean design was applied to produce a limited edition image. The main media that used to reposition the Shibotik brand are Instagram and websites, magazine, look books and store designs as supporting media. Hopefully with the Shibotik brand repositioning, the brand will have a new position as an innovative limited edition batik product.